Muslim world in encountering the challenges of global extremism and terrorism - Abdul Razak, Mohd Abbas; Haneef, Sayed Sikandar Shah; Muhamad Shukri, Abdul Salam (Zes Rokman Resources, 2019)
Extremism and terrorism are not new phenomena that humanity has to deal with. They have been there in the history of mankind ever since the human population started to increase on this planet. In the past, there have been despotic leaders, individuals, and groups of people who used extremism and terrorism as a means to exterminate others in order to hold onto power and exert their dominance. The researchers of this small-scale qualitative study had critically analyzed what is happening to the Muslims and what needs to be done in encountering the challenges of global extremism and terrorism. The researchers took a non-partisan stand in analyzing terrorism in the aftermath of the 9/11 attack that shocked the US and the world at large. The crux of the discussion in this research was centered around on the issues as to why western media take a double standard in reporting terror attacks around the globe, why the oppressed and displaced people of the world resort to terrorism, are terrorists born or made, what lessons can be learned by countries that are faced with terror attacks and racial tensions from role-model countries that are successful in maintaining peace and harmony within their diverse population. Besides discussing the main issues, the researchers have put forward their idealism for world peace and on how the world should stand united in combatting the alarming rate of extremism and terror attacks that happen all over the world today. Data pertinent to research were collected from print and internet sources and later analyzed by using the textual-analysis method. This research has brought to light that extremism and terrorism cannot be eliminated by simply using brute force and bombing campaigns. Countries embroiled with terror attacks need to study objectively the underlying factors that trigger extremism and terrorism.